Patterns of viewing behaviour during advertisement breaks in different television programmes : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Marketing at Massey University - Syn, Maureen (Massey University, 2002)
This thesis sets out to examine the viewing behaviour of television audiences during advertising breaks. The results reported are based on the analysis of in-home video recordings of 14 families watching television in their own homes over an 8-day period. In total, the viewing of 6017 advertisements was examined, and the status of the viewer was recorded at 3-second intervals. Each 3-second observation was accorded one of four possible states: the viewers were directing their attention to the screen (EOS only); they were directing their attention to the screen but engaging in additional behaviours (EOS + behaviour); they were not directing their attention to the screen (No EOS); or they were not present. Across all advertisements, visual attention to the screen was generally low, despite viewers being present for a high proportion of the time during the ad breaks. Viewers were present during the ad breaks for 78% of the time, but were only paying attention to the screen fully 14% (EOS only), and looking as well as doing something else simultaneously 11% of the time (EOS + behaviour). About half the time during the ad break (52%), no one was looking at the screen. However, more significantly for advertisers, ad-viewing behaviour differed by programme type. For example, some programmes could command as much as eight times the proportion of eyes-on-screen time than other programmes. Moreover, the proportions of particular ad-viewing behaviour differ in an unpredictable way for different programmes. Thus different conclusions might be reached when for an example, an advertiser sought to optimise a media plan in terms of EOS only than when the choice was made to optimise another characteristic of ad viewing, say eye-on-screen and doing something else simultaneously (EOS + behavior). In examining three specific methods of classifying programmes, none of them provided workable descriptions of ad-viewing behaviour. This problem manifests itself in a number of ways, but primarily, the aggregation of programmes into categories masks considerable within-group variation, pointing to the need to consider the effect of programmes at a much more disaggregate level, perhaps even to the extent of considering each episode or segment of the programme before the ad break separately. Thus, this research has raised questions about programme ratings and demonstrated that the size of an audience may not reflect how attentive that audience is. Even programmes of small audience sizes may have a high proportion of attentive ad viewers and may thus be of interest to advertisers since advertisements placed within such programmes may be equally (if not more) effective than programmes with a larger audience size.
Keywords: Television advertising; Television viewers; Marketing; Viewing behaviour; Fields of Research::350000 Commerce, Management, Tourism and Services::350200 Business and Management